Effects of Topical Copper Tripeptide Complex on Wound Healing in an Irradiated Rat Model. Issue 3 (6th June 2013) - Parker, Noah P.; Ardeshirpour, Farhad; Schmechel, Stephen C.; Lassig, Amy Anne D.
Abstract : Objectives: To evaluate clinical and immunohistopathological effects of topical glycyl‐histidyl‐lysine‐copper (GHK‐Cu) on in vivo irradiated rat wounds. Design: Animal model. Setting: Academic institution. Subjects and Methods: After dorsal irradiation and a 28‐day recovery period, 2 × 8 cm cranially based dorsal flaps were created in Sprague‐Dawley rats. Twice daily GHK‐Cu gel (test) or aquaphilic ointment (control) was applied for 10 days. Animals were euthanized, digital images of flaps were taken, and harvested tissues were immunohistochemically stained for a vascular endothelium marker, caveolin‐1, and vascular endothelial growth factor (VEGF). Digital image analysis was used for outcome measures. Unpaired t ‐tests were used for statistical analyses; significance of P <. 01 accounted for multiple comparisons. Results: By digital analysis of clinical images, 13 test and 10 control animals showed mean ischemic areas of 5.0 cm 2 (SD = 0.9) for tests and 3.8 cm 2 (SD = 1.1; P =. 011) for controls. Whole slide digitized images allowed quantification of caveolin‐1‐stained blood vessels and VEGF expression in fibroblasts at the interface of healing flaps. Caveolin‐1 analyses showed a mean of 209.0 vessels (SD = 111.1) and a mean vessel luminal area of 525.7 um 2 (SD = 191.0) in tests and 207.4 vessels (SD = 109.4; P =. 973) and 422.8 um 2 (SD = 109.7; P =. 118) in controls. VEGF quantified as the percentage of pixels exceeding a colorimetric threshold, with higher fractions of positive pixels indicating more intense staining, showed a mean intensity score of 0.34 (SD = 0.19) in tests and 0.54 (SD = 0.41; P =. 169) in controls. Conclusions: Irradiated dorsal rat flaps treated with topical GHK‐Cu gel demonstrated no difference in flap ischemia, blood vessel number or area, or VEGF expression compared to controls.